Peningkatan Kreativitas Seni Rupa Anak Usia 5-6 Tahun Melalui Kolase Daun - Fitria, Lutfiana; Siti Kurniasih (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
Early childhood fine arts creativity at PAUD IT Tunas Harapan has not developed optimally, especially in fine arts creativity as evidenced by children still having difficulty in distinguishing colors, lack of children's creativity during learning activities and lack of children's imagination, and only fixated on the teacher's example. Based on these problems, researchers are interested in improving fine arts creativity in children using leaf collage media at PAUD IT Tunas Harapan Village Gedung Mulya Mesuji Regency. The formulation of the problem in this study is